Efektifitas Ekstrak Gel Ikan Haruan Dan Ikan Kembung Terhadap Penyembuhan Luka Pasca Penvabutan Gigi Pada Tikus Putih - naning K utami; metty amperawati (Politeknik Kementerian Kesehatan Banjarmasin, 2018)
All this time albumin given as a treatment therapy derived from human albumin serum produced from human blood. Therefore in the process of making albumin from human blood is very difficult, so this have consequences in the high price of serum albumin (Ignativicius & Workman, 2006). On haruans usually contains a lot of albumin and on bloated fishes contains a lot of essential fatty acids. This research aims at the healing effectiveness of haruan and bloated fish gel extract for the wound of post-dental extraction on white mice. This research is purely experimental research (true experimental), research done with research population is white mice, while the sample research based on the formula there are 8 samples of white mice divided in 2 (two) groups. The data collection is done after white mice's teeth are extracted and every single day smeared with haruan and bloated fish gel extract the measured with vernier calipers and ruler for 10 days. The data were analyzed by statistical analysis with anova test. From the research conducted did not show significant result of healing on the application of haruan and bloated fish gel extract for the wound of post-dental extraction, which obtained significant value (p = 0,401, p> 0,005) for haruan gel extract whereas for bloated fish gel extract obtained a significant value (p = 0.773, p> 0.005). The result of the research showed effectiveness the application of haruan and bloated fish gel extract for the wound of post-dental extraction was insignificant, only on the application of haruan gel extract the wound was reduced and healed by the fifth day.